2022
DOI: 10.1111/soc4.13006
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Offering Wasta: Inferences from Narratives

Abstract: There is increasing interest in understanding Wasta and its influences on individuals and organizations alike, but little attention has been paid to uncovering elements related to the psychology of offering Wasta, to understand how individuals make their decisions about being Wasta patrons.Extending on the article "Narrative inquiry: a proposed methodology for Wasta research" in Thunderbird International Business Review Journal, this article presents a set of narratives of five individuals in various occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This second kind of wasta is, therefore, more powerful. However, a recent study by Al-Twal (2022) revealed that offering wasta sometimes depends on the type of network with the receiver, arguing that it is affected by three conditions: (1) willingness to offer wasta as a simple act of kindness (as in helping others) and in which there are no restrictions to doing so (e.g. institutional factors such as rules preventing the use of wasta); (2) willingness to offer wasta because of potential future returns; thus, if a provider expects something back from the receiver, regardless of the strength of their tie, he will be more inclined to offer wasta and (3) unwillingness to offer wasta regardless of the type of the network or the existence of barriers to its use, because of a personal conviction that the act (i.e.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…This second kind of wasta is, therefore, more powerful. However, a recent study by Al-Twal (2022) revealed that offering wasta sometimes depends on the type of network with the receiver, arguing that it is affected by three conditions: (1) willingness to offer wasta as a simple act of kindness (as in helping others) and in which there are no restrictions to doing so (e.g. institutional factors such as rules preventing the use of wasta); (2) willingness to offer wasta because of potential future returns; thus, if a provider expects something back from the receiver, regardless of the strength of their tie, he will be more inclined to offer wasta and (3) unwillingness to offer wasta regardless of the type of the network or the existence of barriers to its use, because of a personal conviction that the act (i.e.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This second kind of wasta is, therefore, more powerful. However, a recent study by Al-Twal (2022) revealed that offering wasta sometimes depends on the type of network with the receiver, arguing that it is affected by three conditions: (1) willingness to offer wasta as a simple act of kindness (as in helping others) and in which there are no restrictions to doing so (e.g. institutional factors such as rules preventing the use of wasta);…”
Section: Wasta Culture and Economic Challengesmentioning
confidence: 99%
“…The need for wasta is present in many aspects of people's lives in these collectivist cultures and its use is vital in a range of situations, from obtaining access to privileged and classified information to arranging marriages and resolving family and communal conflicts (Ali & Weir, 2020; Cunningham & Sarayrah, 1993), from bypassing the long red tape of governmental procedures to securing business deals, jobs, and promotions (Abosag & Ghauri, 2022; Ali & Weir, 2019; Al‐Twal, 2021; Al‐Twal, 2022). Using one's wasta eludes to a sense of pride while pity is shown towards people who lack this privilege (Cunningham & Sarayrah, 1993).…”
Section: Theoretical Foundation Of Wasta Informal Network and The Ins...mentioning
confidence: 99%
“…A few researchers have highlighted some positive outcomes of using wasta. On the micro level these include obtaining access to privileged and classified information (Ali & Weir, 2020; Cunningham & Sarayrah, 1993), reducing transactional costs and increasing access to services (Alhussan & AL‐Husan., 2022), and gaining employment and promotions (Ali & Weir, 2019; Al‐Twal, 2021; Al‐Twal, 2022). On the miso and macro levels wasta's benefits to organizations range from bypassing the long red tape of governmental procedures to securing business deals (Alhussan & AL‐Husan., 2022; Ali & Weir, 2019).…”
Section: Theoretical Foundation Of Wasta Informal Network and The Ins...mentioning
confidence: 99%
“…To mitigate and reduce the effects of Wasta , Al-Twal (2022) suggests that solid governance and value systems need to be established, as well as fostering the creation of professional networks within organizations. On the other hand, Alsarhan (2022) proposed a roadmap for containing and combating Wasta in the various areas where this practice is developing.…”
Section: Introductionmentioning
confidence: 99%